Enhanced rock-slope failure following ice-sheet deglaciation:timing and causes - Ballantyne, Colin; Wilson, Peter; Gheorghiu, Delia; Rodés, Àngel (Earth Surface Processes and Landforms, 2014)
The temporal pattern of rock-slope failures (RSFs) following Late Pleistocene deglaciation on tectonically stable terrains is controversial: previous studies variously suggest (1) a rapid response due to removal of supporting ice (‘debuttressing’), (2) a progressive decline in RSF frequency, and (3) a millennial-scale delay before peak RSF activity. We test these competing models through beryllium-10 (10Be) exposure dating of five closely-spaced quartzite RSFs on the Isle of Jura, Scotland, to establish the relationship between timing of failure and those of deglaciation, episodes of rapid warming and periods of rapid glacio-isostatic uplift. All five dated RSFs occurred at least 720–2240 years after deglaciation, with the probability of failure peaking ~2 ka after deglaciation, consistent with millennial-scale delay model (3). This excludes debuttressing as an immediate cause of failure, though it is likely that time-dependent stress release due to deglacial unloading resulted in progressive development of failure planes within the rock. Thaw of permafrost ice in joints is unlikely to have been a prime trigger of failure as some RSFs occurred several centuries after the onset of interstadial warming. Conversely, the timespan of the RSFs coincides with the period of maximum glacio-isostatic crustal uplift, suggesting that failure was triggered by uplift-driven seismic events acting on fractured rock masses. Implications of this and related research are: (1) that retreat of the last Pleistocene ice sheets across tectonically-stable mountainous terrains was succeeded by a period of enhanced rock-slope failure due to deglacial unloading and probably uplift-driven seismicity; (2) that the great majority of RSFs in the British Isles outside the limits of Loch Lomond Stadial (= Younger Dryas) glaciation are of Lateglacial (pre-Holocene) age; and (3) numerous RSFs must also have occurred inside Loch Lomond Stadial (LLS) glacial limits, but that runout debris was removed by LLS glaciers.